Semantic and structural displacement in the poem "I am leaving" by the poet Rawda Al-Hajj - Breamh, Sara Ahmed (Journal of Arabic Language Sciences and Literature, 2024)
This study investigates the concept of displacement in Rouba Al-Hajj’s poem "I Am Departing," positing it as a central element that enhances the poem’s aesthetic qualities. Through a close reading and analysis of the text, the research aims to achieve a comprehensive understanding of its constituent parts, thereby uncovering the underlying meanings and connotations. The analysis delves into the poet’s construction of departure and the identity of the persona she creates. To initiate this exploration, the study first provides a theoretical background on displacement. Subsequently, it conducts a meticulous examination of both semantic and structural displacements within the poem. Methodologically, the research adopts a descriptive-analytical approach, culminating in several key findings. Firstly, the study highlights Al-Hajj’s linguistic mastery, where her manipulation of language transcends conventional boundaries, expanding the reader’s cognitive scope. Secondly, the analysis reveals that the departure articulated by the poet encompasses both metaphysical and sensory dimensions, creating a multifaceted experience. Thirdly, it emphasizes the poem’s rich tapestry of imagery and lexicon, employed to evoke novel semantic associations. Furthermore, the study identifies instances of semantic displacement through the consistent use of figurative language. Additionally, it reveals structural displacement manifested in the unconventional treatment of ideas and meanings, deviating from established norms. Finally, the research underscores the dynamic interplay between word arrangement and structural modifications within the poem, which exhibit variations in presentation, temporality, and emphasis through both inclusion and omission.